Supramolecular Germicide Switches through Host‐Guest Interactions for Decelerating Emergence of Drug‐Resistant Pathogens. Issue 26 (12th September 2017) - Bai, Haotian; Fu, Xuancheng; Huang, Zehuan; Lv, Fengting; Liu, Libing; Zhang, Xi; Wang, Shu
Abstract: Infections caused by drug‐resistant pathogens have posed a series of public health crises across the world. To address this challenging issue, development of new antibiotics is one of the most effective methods, however it always lags behind the spreading of antibiotic resistance unfortunately. In this work we illustrate an innovative supramolecular strategy to design germicide switch for decelerating the emergence of drug‐resistant bacteria. The germicide switches are built up between commercial germicides and cucurbit[7]uril (CB[7]) through host‐guest interactions, and their bactericidal activity is switched "off" and "on" reversibly by assembly and dis‐assembly processes of germicide/CB[7] complex. Structure‐property relation exhibits that the interaction between active sites of germicides and CB[7] plays a decisive role in the antimicrobial activity of these germicide switches. By turning antibacterial activity "on" when needed and turning it "off" when not needed, the germicide switch will not continue to produce pressure on bacteria, thus decelerating the emergence of drug‐resistant bacteria. This work offers a proof‐of‐concept approach to efficiently prevent the emergence of drug‐resistant bacteria by controllable and reversible release and concealment of active sites of germicides by supramolecular strategy. Abstract : A supramolecular strategy of commercial germicide is illustrated for decelerating the emergence of drug‐resistant bacteria. The supramolecular germicides are built up between commercial germicides and cucurbit[7]uril (CB[7]) through host‐guest interactions, and their bactericidal activity is switched "off" and "on" reversibly by assembly and dis‐assembly processes. By turning antibacterial activity "on" when needed and turning it "off" when not needed, the supramolecular germicide will not continue to produce pressure on bacteria, thus decelerating the emergence of drug‐resistant bacteria.